(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Introduction: Fractures & Orthopaedic trauma to the new born baby during birth are not uncommon. Immediate unavailability of an Orthopaedic surgeon adds to the embarrassment of the Obstetrician, and creates tension of the parents. Simple early measures can be taken to ease the situation. This paper is prepared with the intention of discussing some of the more common situations & their immediate management. Materials & Methods: Few patients with different birth trauma were treated in Dhaka Medical College Hospital & some other government & non government hospitals during January 2009 to June 2014. Different types of fractures, epiphyseal separation, Obstetric brachial Plexus palsy, Congenital Muscular Torticolis were treated by traction, splinting, plasters, physiotherapy & other conservative methods. Patients were followed up for long term assessment. Results: Results of fracture management were excellent with early union of all the cases. Soft tissue trauma, like Congenital Muscular Torticolis & Obstetric brachial plexus palsy treatment yielded variable results owing to the depth of their involvement. Conclusion: Despite all the measures, trauma to the newborn baby still happens worldwide. Situation in Bangladesh is probably still worse. Early management of birth trauma is essential to avoid a lifelong disability. Immediate management may be started by the obstetrician before referring the patient, which will improve the final outcome. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21025